1996
DOI: 10.1021/ic950482t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Chemical and Electrochemical Characterization of Fe−S Carbonyl Clusters. X-ray Crystal Structures of [N(PPh3)2]2[Fe5S2(CO)14] and [N(PPh3)2]2[Fe6S6(CO)12]

Abstract: A reinvestigation of the redox behavior of the [Fe(3)(&mgr;(3)-S)(CO)(9)](2)(-) dianion led to the isolation and characterization of the new [Fe(5)S(2)(CO)(14)](2)(-), as well as the known [Fe(6)S(6)(CO)(12)](2)(-) dianion. As a corollary, new syntheses of the [Fe(3)S(CO)(9)](2)(-) dianion are also reported. The [Fe(5)S(2)(CO)(14)](2)(-) dianion has been obtained by oxidative condensation of [Fe(3)S(CO)(9)](2)(-) induced by tropylium and Ag(I) salts or SCl(2), or more straightforwardly through the reaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In Homoleptic carbonyl transition metal clusters show little propensity for multiple redox changes. [1Ϫ3] Only some ex-other cases, such as [Co 13 C 2 (CO) 30 ] nϪ and [Co 9 Si(CO) 23 ] nϪ , a synergy between steric (good fit of the cavity) and elecceptional compounds feature different (three or more) oxidation states which are stable, or sufficiently long-lived, to tronic (extra-stabilisation arising from CoϪC or CoϪSi bonds) effects seems to be operative. permit isolation or spectroscopic characterisation of the species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Homoleptic carbonyl transition metal clusters show little propensity for multiple redox changes. [1Ϫ3] Only some ex-other cases, such as [Co 13 C 2 (CO) 30 ] nϪ and [Co 9 Si(CO) 23 ] nϪ , a synergy between steric (good fit of the cavity) and elecceptional compounds feature different (three or more) oxidation states which are stable, or sufficiently long-lived, to tronic (extra-stabilisation arising from CoϪC or CoϪSi bonds) effects seems to be operative. permit isolation or spectroscopic characterisation of the species.…”
Section: Introductionmentioning
confidence: 99%
“…In particular Fe 8 (CO) 32 ] nϪ (n ϭ 3, 4, 5), [7] and [AuFe 4 (CO) 16 ] nϪ (n ϭ 1, the former two homometallic clusters undergo two consecu-2, 3); [8] a few more associate group 14Ϫ16 elements, e.g. tive pairs of close-spaced one-electron reductions, as well as [Co 13 C 2 (CO) 30 ] nϪ (n ϭ 3, 4, 5, 6), [9,2c] [Co 9 Si(CO) 23 ] nϪ (n ϭ two close-spaced one-electron oxidations. Several of the 2, 3, 5), [10] [Ni 11 Bi 2 (CO) 18 ] nϪ (n ϭ 2, 3, 4), [11] above redox changes display features of electrochemical re-[Ni 13 Sb 2 (CO) 24 ] nϪ (n ϭ 2, 3, 4), [12] and [Fe 5 S 2 (CO) 14 ] nϪ versibility, even if most electrogenerated species are only (n ϭ 0, 1, 2), [13] in their cluster cores.…”
Section: Introductionmentioning
confidence: 99%
“…[{Fe(ox-phS) 2 [18] [{Fe(Fe 2 S 2 CO 6 )} 2 (µ-S) 2 ] 2-S 4 2.198(2) NA [a] 2.675(2) 104.96 (7) 74.98(7) [19] [{FeCl 2 } 2 (µ-S) 2 ] [17] [a] NA = not available. (Table 3), confirming previous studies where the {Fe 2 S 2 } core was found nearly invariant to the nature of the terminal ligands.…”
Section: Synthesis and X-ray Diffraction Analyses Of Products 1-3mentioning
confidence: 99%
“…(Table 3), confirming previous studies where the {Fe 2 S 2 } core was found nearly invariant to the nature of the terminal ligands. [17][18][19] It is known from the literature that the reaction of FeCl 3 with dithiols, hydrogen sulfide and sodium methoxide in methanol affords the dimeric Fe…”
Section: Synthesis and X-ray Diffraction Analyses Of Products 1-3mentioning
confidence: 99%
“…Both compounds form a 14-membered ring. The clusters consist of a central [Fe 6 A C H T U N G T R E N N U N G (m 3 -S) 6 (CO) 12 12 ] 2À core has been reported previously as ammonium or bis(triphenylphosphine)iminium salts, which were prepared in a much different way starting from the iron-sulfur-carbonyl dianions [Fe 3 S(CO) 9 ] 2À , [23] [Fe 5 S 4 (CO) 12 ] 2À , [24] or K 2 S 4 . [25] A coordina-tion of the [Fe 6 S 6 (CO) 12 ] 2À core to another metal is so far not known.…”
mentioning
confidence: 99%